2009
DOI: 10.1161/circulationaha.108.808311
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet Therapy and Stent Thrombosis After Sirolimus-Eluting Stent Implantation

Abstract: Background-The influences of antiplatelet therapy discontinuation on the risk of stent thrombosis and long-term clinical outcomes after drug-eluting stent implantation have not yet been addressed adequately. Methods and Results-In an observational study in Japan, 2-year outcomes were assessed in 10 778 patients undergoing sirolimus-eluting stent implantation. Data on status of antiplatelet therapy during follow-up were collected prospectively. Incidences of definite stent thrombosis were 0.34% at 30 days, 0.54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
203
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 344 publications
(224 citation statements)
references
References 24 publications
18
203
2
1
Order By: Relevance
“…Clinical results after PCI with first-generation SES have been reported in many large randomized controlled trials, clinical registries, and small single-center series (Table III, Supporting Information Appendix) [10][11][12][13]. Our data confirm the safety and efficacy of PCI using first-generation SES, extending previous observations in a very large consecutive and unselected cohort of DM patients.…”
Section: Discussionsupporting
confidence: 85%
“…Clinical results after PCI with first-generation SES have been reported in many large randomized controlled trials, clinical registries, and small single-center series (Table III, Supporting Information Appendix) [10][11][12][13]. Our data confirm the safety and efficacy of PCI using first-generation SES, extending previous observations in a very large consecutive and unselected cohort of DM patients.…”
Section: Discussionsupporting
confidence: 85%
“…9,[55][56][57] Although East Asian patients have a higher prevalence of high on-treatment platelet reactivity during clopidogrel treatment than white patients, 9,51 the incidence of adverse ischaemic outcomes or stent thrombosis after PCI is similar or lower than that in white patients. [58][59][60][61] Analysis of data from the US National Cardiovascular Data Registry showed that Asian patients undergoing coronary stent implantation had a lower adjusted risk for the compo site end point of death, MI, and repeat revascularization than white patients (HR 0.89, 95% CI 0.82-0.96, P value not given). 58 In this analysis, the individual end point of death was slightly lower in Asian patients than in white patients, and the incidence of MI was similar in each group.…”
Section: Consensus Statementsmentioning
confidence: 99%
“…The incidence of stent thrombosis reported in South Korean and Japanese registries (~0.2% per year) is lower than that in Western registries (~0.6% per year) after first-generatio n drugeluting stent implantation. [59][60][61] This finding of a higher prevalence of high on-treatment platelet reactivity, but a thrombotic event rate after PCI that is similar or lower in East Asian patients than in white patients, has been called the 'East Asian paradox' . 9 Multiple factors are likely to be associated with the differences in thrombogenicity between East Asian and white individuals, and might explain the variation in propensity for thrombosis.…”
Section: Consensus Statementsmentioning
confidence: 99%
“…In a recent study of healthy Westerners, the prevalence of carriers of the CYP2C19 reduced-function allele was 30% in the total study population 14) . However, adverse cardiovascular events, including stent thrombosis after primary or elective PCI, are lower in Japanese individuals than in Westerners [39][40][41] , although the frequency of carriers of at least one CYP2C19 reduced-function allele is higher in Japanese patients than Western patients. The reason for the low risk of adverse cardiovascular events, including stent thrombosis, in Japan remains unknown; however, it is possible that other factors, such as the PCI procedure, the characteristics of the culprit coronary plaques or coronary risk factors, in addition to platelet aggregation, may influence the clinical outcomes of CAD patients treated with clopidogrel.…”
Section: Disclosuresmentioning
confidence: 92%